2018
DOI: 10.1080/10253890.2018.1510485
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in familial caregivers of Alzheimer’s disease patients: are the effects of chronic stress on cognition inevitable?

Abstract: Familial caregivers of Alzheimer's disease (AD) patients experience an emotional and physical burden which characterizes a chronic stress condition. The resulting hypothalamic-pituitary-adrenal axis dysfunction favors an imbalance of neurotoxic/neuroprotective factors and causes cognitive impairments, increasing the caregivers' risk for cognitive decline and compromising their ability to provide adequate care of the patient. Therefore, the present study aimed to investigate the reversibility of the cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 64 publications
(93 reference statements)
0
20
1
2
Order By: Relevance
“…Prior research has suggested that during earlier stages of cognitive decline, subtle memory complaints may not have a functional impact, although it has been reported that poor results obtained in MFE-30 may be an indicator of future development of dementia [37,47]. Many studies directed to analyze the impact of caregiving on cognition have focused on the effects of taking care of people with dementia suggesting that caregivers display greater vulnerability to cognitive decline [32,48].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has suggested that during earlier stages of cognitive decline, subtle memory complaints may not have a functional impact, although it has been reported that poor results obtained in MFE-30 may be an indicator of future development of dementia [37,47]. Many studies directed to analyze the impact of caregiving on cognition have focused on the effects of taking care of people with dementia suggesting that caregivers display greater vulnerability to cognitive decline [32,48].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that this pandemic could be long-lasting and that the mental health of caregivers of patients with cognitive decline/dementia has been demonstrated to be at risk regardless of the COVID-19 emergency (De Fazio et al, 2015;Corrêa et al, 2019;Lloyd et al, 2019), there is a need to investigate the real effects of the current emergency on caregivers of patients with dementia to identify and address adequate interventions (Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The detrimental influences of informal caregiving on the physical, psychological, and social wellbeing of dementia caregivers are well documented in previous investigations. Specifically, family caregivers of PWD were found to have higher risks of atherosclerosis [ 34 , 35 , 36 , 37 ], poorer physical health conditions [ 4 , 10 , 38 ], cognitive impairments [ 6 , 7 , 8 , 9 ], and poorer psychological health including stress [ 39 ], depression, and anxiety [ 13 , 40 , 41 , 42 ]. Consistent with the aforementioned studies, our study showed that caregivers of PWD had higher prevalence of hypertension, diabetes mellitus, subjective cognitive decline, and depression than noncaregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Family caregivers of PWD are more likely than family caregivers of people without dementia to help with emotional or mental health problems (41% versus 16%) and behavioral issues (15% versus 4%) [2]. Previous studies also documented psychological stress, depressive symptoms, and cognitive impairments in verbal memory, attention, and executive function in family caregivers of PWD [5][6][7][8][9][10][11][12], which may be attributed to their sleep disturbances [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%